The Talmud: Talmud Bavli: The Steinsaltz Edition: Vol 2: Tractate Bava Metzia: Part 2 - Adin Steinsaltz; V. Berman; Baruch Goldberg (USA Random House, 1990)
An overview providing guidelines for study and reading of the Talmud.
Reference guide. -- v. 1-<5>. Tractate Bava Metzia, pt. 1-<5> -- v. 7-12. Tractate Ketubot, pt. 1-6 -- v. 13-14. Tractate Ta'anit, pt. 1-2. -- v. 15-<20>. Tractate Sanhedrin, pt. 1-<6>
English, Hebrew, and Aramaic.
Accompanied by a reference guide.
Keywords: Holy Bible Commentary Series (3SdGSd JaSjQ GdcJGH GdebOSs; Bible